Preparation method and application of blade dislocation line associated high-density electron spin wave type oxide catalyst

By introducing heavy rare earth Y and the forward transition group Mn into the Ru-based catalyst, a RuMnYO2 oxide catalyst with blade-type dislocation lines was prepared, which solved the problem of poor stability of the Ru-based catalyst, achieved high activity and high stability electrocatalytic performance, had the potential to replace iridium dioxide, and the synthesis process was simple and easy to perform.

CN119685851AActive Publication Date: 2025-03-25BEIJING UNIV OF CHEM TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411875055.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing Ru-based catalysts have poor stability in the oxygen precipitation electrode reaction, which limits their application in the electrolytic water hydrogen production technology.

Method used

By introducing a co-doping strategy of heavy rare earth Y and the front transition group Mn, a high-density electron spin-wave RuMnYO2 oxide catalyst with blade-type dislocation lines was prepared, and the electrocatalytic activity and stability of the catalyst were improved by heat-assisted sodium borohydride reducing metal precursors and polyaniline coating.

Benefits of technology

This catalyst exhibits ultra-low overpotential and long-term stability in acidic and neutral water electrolysis. The electrocatalytic activity exceeds commercial iridium dioxide catalysts in all respects. It has the potential to replace iridium dioxide, and the synthesis process is simple and easy to perform, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005196664210000011
    Figure HDA0005196664210000011
  • Figure HDA0005196664210000012
    Figure HDA0005196664210000012
  • Figure HDA0005196664210000021
    Figure HDA0005196664210000021
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a blade dislocation line associated high-density electron spin wave type oxide catalyst, and belongs to the technical field of catalysts. A heavy rare earth Y and front transition group Mn co-doping strategy is adopted, a method of reducing a metal precursor through heat-assisted sodium borohydride and co-pyrolyzing after polyaniline coating is adopted, meanwhile, a large-size rare earth element and a small-size front transition group metal element are introduced to generate a large number of Cottell air mass type blade dislocation lines in Ru-based oxide, atomic-scale elastic stress / strain waves are generated, and the Cottell air mass type blade dislocation lines are formed. According to the present invention, the process of electron spin polarization of active metal around the dislocation line and doping reinforcement of Y and Mn is performed so as to achieve electron enrichment of the active metal near the dislocation line, such that the associated high-density electron spin wave is formed in the blade-type dislocation line structure so as to provide the high-activity and high-stability catalysis site for oxygen evolution;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hydrogen production by water electrolysis in energy applications, and specifically relates to a method for preparing a high-density electron spin wave-type oxide catalyst associated with edge dislocation lines and its application in acidic and neutral water electrolysis. The catalyst has high electrocatalytic activity and long-term stability, and is used as an efficient catalyst for anode oxygen precipitation in proton exchange membrane water electrolysis hydrogen production technology. Background Art

[0002] Hydrogen has always been recognized as the most ideal green energy matrix, with the characteristics of abundant sources, cleanliness, and renewableness. Therefore, the development of hydrogen energy has become a research hotspot in the energy field. There are many ways to obtain hydrogen energy. Traditionally, it can be divided into two categories based on the source of raw materials: one is to use mineral resources (such as coal, oil or natural gas, etc.) as raw materials, and to produce hydrogen through reforming or partial oxidation, but at the same time, CO2 gas that causes the greenhouse effect is generated; the other is to use water as a reactant, and produce hydrogen through electrolysis or pyrolysis. Among them, hydrogen production by water electrolysis is an important source for the preparation of high-purity hydrogen. The oxygen evolution reaction (OER) on the anode of the water electrolysis hydrogen production process has a high overpotential, so a catalyst is required to catalyze it to reduce power loss.

[0003] Currently, only advanced catalysts based on Ru or Ir noble metals can meet the requirements of the harsh environment in deployed PEMWE devices. Compared with expensive Ir-based catalysts, Ru-based catalysts are much cheaper and have higher intrinsic activity, and are considered to be a promising alternative to commercial IrO2. It is believed that RuO2 shows a kinetically favorable lattice oxygen evolution mechanism (LOM) pathway during the OER process in acidic environments. However, the direct evolution of lattice oxygen of the catalyst through the LOM pathway will release some lattice oxygen vacancies (V O ), leading to a soluble oxygen vacancy intermediate (*V O -RuO4 2– ), resulting in Ru ion dissolution and crystal structure collapse. This is because Ru and its oxides have high oxygen evolution performance, but they will dissolve more severely during use and have poor stability, which limits the development of ruthenium-based catalysts in oxygen evolution electrode reactions. Therefore, balancing activity and stability by designing a reasonable composition and coordination structure of ruthenium-based catalysts remains a huge challenge for PEMWE applications.

[0004] Rare earth elements can adjust the electronic structure and surface chemical properties of metals by adjusting the adsorption energy of reaction intermediates, thereby improving the intrinsic activity and stability of catalysts. Rare earth elements have advantages such as large atomic size, good hydrophilicity and unique electronic energy bands. They are called industrial vitamins and are key components for improving the physical and chemical properties of various materials. However, due to the large size of rare earth elements as guests, they are difficult to alloy with Ru due to lattice mismatch, but trace amounts of rare earth elements may lead to unexpected properties of their composite materials. Therefore, if we introduce oxygen-philic rare earth elements (such as Y) into the Ru-based system, the Y atom has a strong binding force with O, which is higher than Ru, which helps to stabilize the lattice oxygen, thereby achieving the stabilization of the catalyst structure. As a pre-transition metal, Mn has a smaller atomic size, which matches the large-sized rare earth Y and gathers in an orderly manner around the oxide edge dislocation, forming a highly stable Cottrel gas-type edge dislocation line, and generating atomic-level elastic stress / strain waves, polarizing the spin state of the active metal electrons around the dislocation line. The doping of Y and Mn strengthens this process, making the active metal near the dislocation line electron-rich, and forming an associated high-density electron spin wave in the edge dislocation line structure, thereby providing highly active and highly stable catalytic sites for oxygen evolution, while improving the activity and long-term stability of acidic water decomposition. The electrocatalytic activity and stability of this catalyst comprehensively surpass commercial iridium dioxide catalysts, and it has the potential to replace iridium dioxide as a catalyst for the oxygen evolution reaction at the anode of water electrolysis hydrogen production. In addition, its synthesis process is simple and easy, and the preparation conditions are not high, which can achieve industrial scale-up production. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art and better improve the catalyst activity and stability at the same time, the present invention proposes a co-doping strategy of heavy rare earth Y and pre-transition group Mn. Through the method of heat-assisted sodium borohydride reduction of metal precursors and polyaniline coating followed by co-pyrolysis, large-sized rare earth elements and small-sized pre-transition group metal elements are simultaneously introduced to generate a large number of Cottrell gas cloud-type edge dislocation lines inside the Ru-based oxide, and generate atomic-level elastic stress / strain waves, so that the spin states of active metal electrons around the dislocation lines are polarized. The doping of Y and Mn strengthens this process, so that the active metal near the dislocation line is electron-rich, and an associated high-density electron spin wave is formed in the edge dislocation line structure, thereby providing highly active and highly stable catalytic sites for oxygen evolution.

[0006] To achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] The present invention also protects a method for preparing the oxide catalyst, comprising the following steps:

[0008] 1) Synthesis of RuMnY alloy by heat-assisted sodium borohydride reduction of metal precursors;

[0009] 2) Pre-treating the surface of the RuMnY alloy to polymerize the aniline monomer on the alloy surface to obtain a polyaniline-coated RuMnY alloy (PANI@RuMnY);

[0010] 3) The PANI@RuMnY obtained in step 2) is calcined and oxidized in an air atmosphere to obtain a RuMnYO2 oxide catalyst with high dispersion, uniform particle size and rich dislocations.

[0011] In a preferred embodiment of the present invention, in step (1), the RuMnY alloy is prepared as follows:

[0012] The synthesis of RuMnY alloy co-doped with heavy rare earth Y and pre-transition metal Mn includes three steps of dispersion, reduction and water washing, and finally filtration collection and drying. First, ruthenium salt, manganese salt and rare earth metal Y salt are respectively configured into aqueous solutions (preferably with a concentration of 0.1M), and then mixed and stirred in molar ratio to obtain a salt solution; sodium borohydride solution is configured, and the amount of sodium borohydride is 5 to 10 times the amount of the metal material to be reduced, preferably 5 times; then the obtained salt solution is heated to 30 to 80°C, preferably 60°C, under stirring, and then the prepared sodium borohydride solution is dripped at a uniform speed until the dripping is complete, and the dripping time is controlled within 0.5 to 1h, and then naturally cooled to room temperature to obtain a precipitate. After the reduction is completed, the precipitate is filtered and washed to obtain a solid alloy catalyst; the solid alloy catalyst is dried to obtain a highly dispersed RuMnY alloy with uniform particle size.

[0013] In a preferred embodiment of the present invention, the anions of the ruthenium salt, manganese salt and rare earth metal Y salt are independently selected from one or more of acetate ions, sulfate ions, chloride ions and nitrate ions, preferably chloride ions.

[0014] In a preferred embodiment of the present invention, the molar ratio of ruthenium, manganese and yttrium corresponding to the ruthenium salt, manganese salt and rare earth metal Y salt is 2:2:(0.5-2).

[0015] Furthermore, the preparation method of step 2) comprises the following steps:

[0016] (1) The RuMnY alloy prepared by heat-assisted sodium borohydride reduction of the metal precursor is subjected to polyaniline coating. The prepared RuMnY alloy is added to deionized water for ultrasonic dispersion for 0.5 to 2 hours to ensure that the alloy is evenly dispersed in the solution; an acid solution of aniline and an acid solution of an oxidant are prepared separately, and then the acid solution of aniline and the acid solution of the oxidant are successively added to the RuMnY alloy dispersion, and magnetic stirring is continued for 10 hours under ice bath conditions to polymerize the aniline monomer on the surface of the RuMnY alloy, and the mixture is collected by centrifugation to obtain a polyaniline-coated RuMnY alloy, namely PANI@RuMnY;

[0017] In the acid solution of aniline, every 30 to 60 microliters of aniline corresponds to 5 to 10 ml of the acid solution; in the acid solution of the oxidant, every 60 to 90 mg of the oxidant corresponds to 5 to 10 ml of the acid solution; the concentration of the acid solution is 0.5 to 3 M, and when further preparing the acid solution of aniline and the acid solution of the oxidant, ultrasound is used for 10 to 60 minutes to make them evenly dispersed;

[0018] Every 20-60 mg of RuMnY alloy corresponds to 30-60 μl of aniline and 60-90 mg of oxidant;

[0019] In a preferred embodiment of the present invention, the acid solution comprises one or more of sulfuric acid, nitric acid, hydrochloric acid, oxalic acid, and acetic acid, preferably hydrochloric acid.

[0020] In a preferred embodiment of the present invention, the oxidant includes one or more of ammonium persulfate, potassium dichromate, potassium iodate, ferric chloride, and hydrogen peroxide, preferably ammonium persulfate.

[0021] (2) The PANI@RuMnY obtained in step 1) is washed three times with ethanol, and then dried in an oven at 60-90°C for 5-30 min. After drying, it is calcined in a tube furnace at 350-600°C for 60-180 min in an air atmosphere. After calcination, it is naturally cooled to room temperature in air to obtain a highly dispersed, uniform particle size and dislocation-rich RuMnYO2 oxide catalyst.

[0022] In a preferred embodiment of the present invention, the oxide has a rutile crystal structure type;

[0023] RuMnYO2 oxide in acidic (0.5M H2SO4) water electrolysis 10mAcm -2 The device has an ultra-low overpotential of 188 mV and can operate for 220 hours at a low and stable cell potential. In a proton exchange membrane water electrolysis hydrogen production device under a neutral environment, the device can generate hydrogen at 1 A cm -2 The current density can be operated for 100 h at a low and stable cell potential of 1.62 V without decay.

[0024] The mechanism and beneficial effects of the present invention include:

[0025] (1) Compared with the prior art, the present invention prepares a high-density electron spin wave oxide catalyst with an edge dislocation line through the design of catalyst composition and structure, and applies it to water decomposition catalyst, solving the problem of low conversion efficiency of related reactions. The catalyst has excellent oxygen evolution electrocatalytic activity. It can be used as an electrode electrocatalyst for oxygen evolution reaction in devices such as proton exchange membrane water electrolysis;

[0026] (2) The present invention balances activity and stability by designing a reasonable composition and coordination structure of a ruthenium-based catalyst. Rare earth elements can adjust the electronic structure and surface chemical properties of metals by adjusting the adsorption energy of reaction intermediates, thereby improving the intrinsic activity and stability of the catalyst. Rare earth elements have advantages such as large atomic size, good hydrophilicity and unique electronic energy bands. They are called industrial vitamins and are key components for improving the physical and chemical properties of various materials. However, since rare earth elements have a large size as guests, they are difficult to alloy with Ru due to lattice mismatch, but trace amounts of rare earth elements may lead to unexpected properties of their composite materials. When oxygen-philic rare earth elements (such as Y) are introduced into the Ru-based system, the Y atom has a strong binding force with O, which is higher than Ru, and helps to stabilize the lattice oxygen, thereby achieving stabilization of the catalyst structure. As a pre-transition metal, Mn has a smaller atomic size, which matches the large size of rare earth Y and gathers in an orderly manner around the oxide edge dislocation, forming a highly stable Cottrel gas-type edge dislocation line, and generating atomic-level elastic stress / strain waves, polarizing the spin state of the active metal electrons around the dislocation line. The doping of Y and Mn strengthens this process, making the active metal near the dislocation line electron-rich, and forming an associated high-density electron spin wave in the edge dislocation line structure, thereby providing highly active and highly stable catalytic sites for oxygen evolution, while improving the activity and long-term stability of acidic water decomposition. The electrocatalytic activity and stability of this catalyst comprehensively surpass those of commercial iridium dioxide catalysts, and it has the potential to replace iridium dioxide as a catalyst for the oxygen evolution reaction at the anode of water electrolysis to produce hydrogen. In addition, its synthesis process is simple and easy, and the preparation conditions are not high, which can achieve industrial scale-up production. This work may open the door to the development of advanced OER catalysts through controllable composition design and microstructure reconstruction, while improving the activity and long-term stability of acidic water decomposition.

[0027] (3) The present invention uses a method of heat-assisted sodium borohydride reduction of metal precursors and polyaniline coating followed by co-pyrolysis to prepare a RuMnYO2 oxide catalyst with uniform particle size, good dispersion and high-density electron spin wave associated with edge dislocation lines. The obtained RuMnYO2 oxide has a high electron spin wave capacity of 10 mA cm -2 The ionization temperature is 10000 ℃ and the overpotential is 188 mV, which is 105 mV lower than that of commercial IrO2. Importantly, it can be used at 10 mA cm -2 The device was operated at a low and stable potential (1.52 V ± 0.08 V) for 220 h at a current density of 1.5 V, which is 8 times the stability of the state-of-the-art commercial IrO2. -2 The current density can be operated for 100 h at a low and stable cell potential of 1.62 V without decay. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described below in conjunction with the accompanying drawings. The accompanying drawings are only used to schematically illustrate and explain the present invention and do not limit the scope of the present invention.

[0029] Figure 1 The transmission electron microscope (TEM) analysis images of the RuMnYO2 oxide catalyst in Example 1 at different magnifications.

[0030] Figure 2 X-ray diffraction (XRD) patterns of the four nanocrystalline catalysts with different rare earth Y contents in Examples 1-4.

[0031] Figure 3 The X-ray diffraction (XRD) pattern and dislocation density of the RuMnYO2 oxide catalyst in Example 1.

[0032] Figure 4 This is the inverse fast Fourier transform (IFFT) image of the RuMnYO2 oxide obtained in Example 1, in which clear edge dislocations can be seen.

[0033] Figure 5 This is a spherical aberration transmission electron microscopy image (HAADF-STEM) of the RuMnYO2 oxide obtained in Example 1, in which clear edge dislocation lines can be seen.

[0034] Figure 6 (a) and (b) are spherical aberration transmission electron microscopy images (HAADF-STEM) of the RuMnYO2 oxide obtained in Example 1, and (a') and (b') are the corresponding holographic electron images.

[0035] Figure 7 (a) Oxygen evolution reaction (OER) polarization curves and (b) 10, 50 and 100 mA cm-2 of RuMnYO2 oxides obtained in Examples 1 to 4 with commercial IrO2 -2 Overpotential at current density.

[0036] Figure 8 The RuMnYO2 oxide obtained in Example 1 and the commercial iridium dioxide (IrO2) catalyst were -2 Chronoamperometry stability test at different current densities.

[0037] Fig. 9 This is a test diagram of the stability of the neutral proton exchange membrane electrolysis of RuMnYO2 oxide obtained in Example 1. The electrolyte tested was pure water; the test current density was 1Acm -2 . DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited by the specific embodiments.

[0039] Example 1 (Feeding ratio Ru:Mn:Y=2:2:1.5 (metal atomic ratio))

[0040] (1) Synthesis of RuMnY alloy co-doped with heavy rare earth Y and early transition metal Mn, including three steps of dispersion, reduction, and water washing, and finally filtration, collection, and drying. First, 0.1M aqueous solution of ruthenium salt, manganese salt, and rare earth metal salt are prepared respectively, and then added to the dispersion at a molar ratio of Ru:Mn:Y=2:2:1.5 and stirred for 0.5h. 10ml of sodium borohydride solution is prepared, and the amount of sodium borohydride is 5 to 10 times, preferably 5 times, the amount of metal to be reduced. Then, the obtained black slurry is heated to 30 to 80°C, preferably 60°C, under stirring, and then the prepared sodium borohydride solution is added dropwise at a uniform speed until the addition is complete, and the addition time is controlled within 0.5 to 1h, and then naturally cooled to room temperature to obtain a black precipitate. After the reduction is completed, the black precipitate is filtered and washed to obtain a solid alloy catalyst; the solid alloy catalyst is dried to obtain a highly dispersed RuMnY alloy with uniform particle size.

[0041] (2) The RuMnY alloy prepared in step 1) by heat-assisted sodium borohydride reduction of the metal precursor is subjected to polyaniline coating. 20 mg of RuMnY alloy is added to deionized water and ultrasonically dispersed for 0.5 h to ensure that the alloy is evenly dispersed in the solution. A 0.5 M acid solution containing 30 microliters of aniline and 60 mg of oxidant is prepared respectively, and ultrasonicated for 30 minutes to make the dispersion even. Then, the acid solution containing aniline monomer and oxidant is added to the black slurry successively, and magnetic stirring is continued for 10 h under ice bath conditions to polymerize the aniline monomer on the surface of the RuMnY alloy, and the mixture is collected by centrifugation to obtain a polyaniline-coated RuMnY alloy (PANI@RuMnY).

[0042] (3) The PANI@RuMnY obtained in step 2) was washed three times with ethanol, and then dried in an oven at 60°C for 30 min. After drying, it was calcined in a tube furnace at 500°C for 180 min in an air atmosphere. After calcination, it was naturally cooled to room temperature in air to obtain a highly dispersed, uniform particle size and dislocation-rich RuMnYO2 oxide catalyst.

[0043] Example 2 (Feeding ratio Ru:Mn:Y=2:2:0.5 (metal atomic ratio))

[0044] (1) Synthesis of RuMnY alloy co-doped with heavy rare earth Y and early transition metal Mn, including three steps of dispersion, reduction, and water washing, and finally filtration, collection, and drying. First, 0.1M aqueous solution of ruthenium salt, manganese salt, and rare earth metal salt are prepared respectively, and then added to the uniformly dispersed black slurry at a molar ratio of Ru:Mn:Y=2:2:0.5 and stirred for 0.5-1h. 10ml of sodium borohydride solution is prepared, and the amount of sodium borohydride is 5-10 times, preferably 5 times, of the amount of metal to be reduced. Then, the obtained black slurry is heated to 30-80°C, preferably 60°C, under stirring, and then the prepared sodium borohydride solution is added dropwise at a uniform speed until the addition is complete, and the addition time is controlled within 0.5-1h, and then naturally cooled to room temperature to obtain a black precipitate. After the reduction is completed, the black precipitate is filtered and washed to obtain a solid alloy catalyst; the solid alloy catalyst is dried to obtain a highly dispersed RuMnY alloy with uniform particle size.

[0045] (2) The RuMnY alloy prepared in step 1) by heat-assisted sodium borohydride reduction of the metal precursor is subjected to polyaniline coating. 20 mg of RuMnY alloy is added to deionized water and ultrasonically dispersed for 0.5 h to ensure that the alloy is evenly dispersed in the solution. A 0.5 M acid solution containing 30 microliters of aniline and 60 mg of oxidant is prepared respectively, and ultrasonicated for 30 minutes to make the dispersion even. Then, the acid solution containing aniline monomer and oxidant is added to the black slurry successively, and magnetic stirring is continued for 10 h under ice bath conditions to polymerize the aniline monomer on the surface of the RuMnY alloy, and the mixture is collected by centrifugation to obtain a polyaniline-coated RuMnY alloy (PANI@RuMnY).

[0046] (3) The PANI@RuMnY obtained in step 2) was washed three times with ethanol, and then dried in an oven at 60°C for 30 min. After drying, it was calcined in a tube furnace at 500°C for 180 min in an air atmosphere. After calcination, it was naturally cooled to room temperature in air to obtain a highly dispersed, uniform particle size and dislocation-rich RuMnYO2 oxide catalyst.

[0047] Example 3 (Feeding ratio Ru:Mn:Y=2:2:1 (metal atomic ratio))

[0048] (1) Synthesis of RuMnY alloy co-doped with heavy rare earth Y and early transition metal Mn, including three steps of dispersion, reduction, and water washing, and finally filtration, collection, and drying. First, 0.1M aqueous solution of ruthenium salt, manganese salt, and rare earth metal salt are prepared respectively, and then added to the uniformly dispersed black slurry at a molar ratio of Ru:Mn:Y=2:2:1 and stirred for 0.5-1h. 10ml of sodium borohydride solution is prepared, and the amount of sodium borohydride is 5-10 times, preferably 5 times, the amount of metal to be reduced. Then, the obtained black slurry is heated to 30-80°C, preferably 60°C, under stirring, and then the prepared sodium borohydride solution is added dropwise at a uniform speed until the addition is complete, and the addition time is controlled within 0.5-1h, and then naturally cooled to room temperature to obtain a black precipitate. After the reduction is completed, the black precipitate is filtered and washed to obtain a solid alloy catalyst; the solid alloy catalyst is dried to obtain a highly dispersed RuMnY alloy with uniform particle size.

[0049] (2) The RuMnY alloy prepared in step 1) by heat-assisted sodium borohydride reduction of the metal precursor is subjected to polyaniline coating. 20 mg of RuMnY alloy is added to deionized water and ultrasonically dispersed for 0.5 h to ensure that the alloy is evenly dispersed in the solution. A 0.5 M acid solution containing 30 microliters of aniline and 60 mg of oxidant is prepared respectively, and ultrasonicated for 30 minutes to make the dispersion even. Then, the acid solution containing aniline monomer and oxidant is added to the black slurry successively, and magnetic stirring is continued for 10 h under ice bath conditions to polymerize the aniline monomer on the surface of the RuMnY alloy, and the mixture is collected by centrifugation to obtain a polyaniline-coated RuMnY alloy (PANI@RuMnY).

[0050] (3) The PANI@RuMnY obtained in step 2) was washed three times with ethanol, and then dried in an oven at 60°C for 30 min. After drying, it was calcined in a tube furnace at 500°C for 180 min in an air atmosphere. After calcination, it was naturally cooled to room temperature in air to obtain a highly dispersed, uniform particle size and dislocation-rich RuMnYO2 oxide catalyst.

[0051] Example 4 (Feeding ratio Ru:Mn:Y=2:2:2 (metal atomic ratio))

[0052] (1) Synthesis of RuMnY alloy co-doped with heavy rare earth Y and early transition metal Mn, including three steps of dispersion, reduction, and water washing, and finally filtration, collection, and drying. First, 0.1M aqueous solution of ruthenium salt, manganese salt, and rare earth metal salt are prepared respectively, and then added to the uniformly dispersed black slurry at a molar ratio of Ru:Mn:Y=2:2:2 and stirred for 0.5-1h. 10ml of sodium borohydride solution is prepared, and the amount of sodium borohydride is 5-10 times, preferably 5 times, the amount of metal to be reduced. Then, the obtained black slurry is heated to 30-80°C, preferably 60°C, under stirring, and then the prepared sodium borohydride solution is added dropwise at a uniform speed until the addition is complete, and the addition time is controlled within 0.5-1h, and then naturally cooled to room temperature to obtain a black precipitate. After the reduction is completed, the black precipitate is filtered and washed to obtain a solid alloy catalyst; the solid alloy catalyst is dried to obtain a highly dispersed RuMnY alloy with uniform particle size.

[0053] (2) The RuMnY alloy prepared in step 1) by heat-assisted sodium borohydride reduction of the metal precursor is subjected to polyaniline coating. 20 mg of RuMnY alloy is added to deionized water and ultrasonically dispersed for 0.5 h to ensure that the alloy is evenly dispersed in the solution. A 0.5 M acid solution containing 30 microliters of aniline and 60 mg of oxidant is prepared respectively, and ultrasonicated for 30 minutes to make the dispersion even. Then, the acid solution containing aniline monomer and oxidant is added to the black slurry successively, and magnetic stirring is continued for 10 h under ice bath conditions to polymerize the aniline monomer on the surface of the RuMnY alloy, and the mixture is collected by centrifugation to obtain a polyaniline-coated RuMnY alloy (PANI@RuMnY).

[0054] (3) The PANI@RuMnY obtained in step 2) was washed three times with ethanol, and then dried in an oven at 60°C for 30 min. After drying, it was calcined in a tube furnace at 500°C for 180 min in an air atmosphere. After calcination, it was naturally cooled to room temperature in air to obtain a highly dispersed, uniform particle size and dislocation-rich RuMnYO2 oxide catalyst.

[0055] Figure 1 This is a high-resolution transmission electron microscope (HRTEM) image of the RuMnYO2 oxide catalyst with the best ratio prepared in Example 1. The oxide particle size is about 5.0-10.0 nm, and the distribution is in a coral-like morphology, and a fine-grained ternary oxide catalyst is obtained.

[0056] Figure 2 It is the X-ray diffraction pattern of the catalyst obtained in Example 1-4. It can be seen that within a certain doping range, the RuMnYO2 prepared in Example 1-3 maintains the crystal structure of rutile oxide, and the particle size calculated based on the Scherrer formula is consistent with that observed in the HRTEM image.

[0057] Figure 3 is the X-ray diffraction pattern of the oxide catalyst obtained in Example 1. Based on the XRD pattern, the dislocation densities of the oxide (110), (101), (200), and (211) are 17.79, 20.49, 16.79, and 32.51 nm, respectively. -2 .

[0058] Figure 4 This is the inverse fast Fourier transform (IFFT) image of the RuMnYO2 oxide catalyst with the best ratio obtained in Example 1. It can be seen that the lattice fringes of the four crystal planes corresponding to the oxide and the XRD spectrum are distorted, and edge dislocations of different densities appear, indicating that large-sized rare earth Y and small-sized pre-transition group Mn are orderly arranged inside the Ru-based oxide to produce a large number of Cottrell gas-type dislocation lines. Statistics show that the number of excess half-atomic planes of dislocations per unit area of ​​the oxides (110), (101), (200), and (211) are 0.263, 0.455, 0.184, and 0.921 / nm, respectively. 2 .

[0059] Figure 5 This is a spherical aberration transmission electron microscopy image (HAADF-STEM) of the RuMnYO2 oxide obtained in Example 1, in which clear edge dislocation lines can be seen with a length of about 3-10 nm.

[0060] Figure 6 This is the electron holographic image of the RuMnYO2 oxide catalyst with the best ratio obtained in Example 1. It can be seen that the Ru-based oxide is orderly aggregated inside to produce a large number of Cottrell gas-type dislocation lines, and generate atomic-level elastic stress / strain waves, which polarize the spin states of active metal electrons around the dislocation lines. The doping of Y and Mn strengthens this process, making the active metal near the dislocation lines electron-rich, and forming associated high-density electron spin waves in the edge-type dislocation line structure. The intensity of the spin-delocalized electron wave associated with the dislocation line reaches 20.034%, providing highly active and highly stable catalytic sites for oxygen evolution.

[0061] Figure 7 The polarization curve of the RuMnYO2 oxide catalyst with the best ratio obtained in Example 1 shows that the catalyst has a high conductivity at 10 mA cm -2 The overpotential at a current density of only 188 mV is much lower than the 293 mV of commercial IrO2. And it shows a lower overpotential at a high current density.

[0062] Figure 8 The stability diagram of the RuMnYO2 oxide electrocatalyst with the best ratio obtained in Example 1 shows that the current density is 10 mA cm -2The stability of the RuMnYO2 oxide electrocatalyst can be maintained for more than 220 hours, which is much better than the commercial IrO2 catalyst.

[0063] Fig. 9 This is the stability image of the neutral proton exchange membrane water electrolysis of RuMnYO2 oxide obtained in Example 1 for 100 hours, and maintains a low overpotential.

[0064] The dislocation density of RuMnYO2 oxide measured by X-ray diffraction is 0.016nm. -2 The length of the dislocation line observed by atomic-level microscopy is about 3-10nm, and the number of excess half-atomic planes of dislocation per unit area reaches 0.184 / nm. 2 The above. The large-sized heavy rare earth element Y and the small-sized pre-transition metal element Mn are orderly aggregated inside the Ru-based oxide, generating a large number of Cottrell gas-type edge dislocation lines, and generating atomic-level elastic stress / strain waves, which polarize the spin states of active metal electrons around the dislocation lines. The doping of Y and Mn strengthens this process, making the active metal near the dislocation line electron-rich, and forming an associated high-density electron spin wave in the edge dislocation line structure. The intensity of the spin delocalized electron wave associated with the dislocation line reaches 20.034%, providing highly active and highly stable catalytic sites for oxygen evolution, while improving the activity and long-term stability of acidic water decomposition. It can be seen that this technical solution proposes a novel method for enhancing the performance of acidic water oxidation and oxygen evolution through the coupling design of catalyst components and microstructure regulation, and at the same time solves the problem of the difficulty in balancing the activity and stability of anode catalysts in acidic water electrolysis for hydrogen production, paving the way for the manufacture of high-performance acidic water oxygen evolution catalysts. The developed catalyst is suitable for the field of industrial proton exchange membrane water electrolysis for hydrogen production. The invention involves catalyst preparation technology, which is simple, rapid and environmentally friendly, laying the foundation for future large-scale industrial production and showing that the technology has great application prospects and market potential.

Claims

1. A method for preparing a high-density electron spin wave oxide catalyst associated with edge dislocation lines, wherein: The following steps are involved: 1) Synthesis of RuMnY alloy by heat-assisted sodium borohydride reduction of metal precursors; 2) Pre-treating the surface of the RuMnY alloy to polymerize the aniline monomer on the alloy surface to obtain a polyaniline-coated RuMnY alloy (PANI@RuMnY); 3) The PANI@RuMnY obtained in step 2) is calcined and oxidized in an air atmosphere to obtain a RuMnYO2 oxide catalyst with high dispersion, uniform particle size and rich dislocations.

2. The method according to claim 1, characterized in that In step (1), the RuMnY alloy is prepared as follows: The synthesis of RuMnY alloy co-doped with heavy rare earth Y and early transition metal Mn includes three steps of dispersion, reduction and water washing, and finally filtration collection and drying; firstly, ruthenium salt, manganese salt and rare earth metal Y salt are respectively prepared into aqueous solutions, and then mixed in molar ratio and stirred to obtain a salt solution; A sodium borohydride solution is prepared, wherein the amount of the sodium borohydride is 5 to 10 times, preferably 5 times, the amount of the metal material to be reduced; then the obtained salt solution is heated to 30 to 80° C., preferably 60° C., under stirring, and then the prepared sodium borohydride solution is added dropwise at a uniform speed until the addition is complete, and the addition time is controlled within 0.5 to 1 hour, and then naturally cooled to room temperature to obtain a precipitate. After the reduction is completed, the precipitate is filtered and washed to obtain a solid alloy catalyst; the solid alloy catalyst is dried to obtain a highly dispersed RuMnY alloy with uniform particle size; The anions of the ruthenium salt, manganese salt and rare earth metal Y salt are independently selected from one or more of acetate ions, sulfate ions, chloride ions and nitrate ions, preferably chloride ions; The molar ratio of ruthenium, manganese and yttrium corresponding to the ruthenium salt, manganese salt and rare earth metal Y salt is 2:2:(0.5-2).

3. The method according to claim 1, characterized in that The preparation method of step 2) comprises the following steps: (1) The RuMnY alloy prepared by heat-assisted sodium borohydride reduction of the metal precursor is subjected to polyaniline coating. The prepared RuMnY alloy is added to deionized water for ultrasonic dispersion for 0.5 to 2 hours to ensure that the alloy is evenly dispersed in the solution; an acid solution of aniline and an acid solution of an oxidant are prepared separately, and then the acid solution of aniline and the acid solution of the oxidant are successively added to the RuMnY alloy dispersion, and magnetic stirring is continued for 10 hours under ice bath conditions to polymerize the aniline monomer on the surface of the RuMnY alloy, and the mixture is collected by centrifugation to obtain a polyaniline-coated RuMnY alloy, namely PANI@RuMnY; (2) The PANI@RuMnY obtained in step 1) is washed three times with ethanol, and then dried in an oven at 60-90°C for 5-30 min. After drying, it is calcined in a tube furnace at 350-600°C for 60-180 min in an air atmosphere. After calcination, it is naturally cooled to room temperature in air to obtain a highly dispersed, uniform particle size and dislocation-rich RuMnYO2 oxide catalyst.

4. The method according to claim 3, characterized in that In the acid solution of aniline, every 30 to 60 microliters of aniline corresponds to 5 to 10 ml of the acid solution; in the acid solution of the oxidant, every 60 to 90 mg of the oxidant corresponds to 5 to 10 ml of the acid solution.

5. The method according to claim 3, characterized in that Every 20 to 60 mg of RuMnY alloy corresponds to 30 to 60 microliters of aniline and 60 to 90 mg of oxidant.

6. The method according to claim 3, characterized in that The acid solution includes one or more of sulfuric acid, nitric acid, hydrochloric acid, oxalic acid, and acetic acid, preferably hydrochloric acid. The concentration of the acid solution is 0.5 to 3 M. When further preparing the acid solution of aniline and the acid solution of the oxidant, ultrasound is used for 10 to 60 minutes to make them dispersed evenly.

7. The method according to claim 3, characterized in that The oxidant includes one or more of ammonium persulfate, potassium dichromate, potassium iodate, ferric chloride, and hydrogen peroxide, preferably ammonium persulfate.

8. The catalyst prepared by the method according to any one of claims 1 to 7, characterized in that: The oxide has a rutile crystal structure; large-sized rare earth Y and small-sized pre-transition group Mn are orderly arranged inside the Ru-based oxide to produce a large number of Cottrell gas-type dislocation lines.

9. Use of the catalyst prepared by the method according to any one of claims 1 to 7 in acidic and neutral water electrolysis.

10. The use of the catalyst prepared by the method according to any one of claims 1 to 7, RuMnYO2 oxide can be electrolyzed in acidic water at 10 mA cm -2 The RuMnYO2 oxide has an ultra-low overpotential of 188 mV and can operate for 220 hours at a low and stable cell potential; RuMnYO2 oxide can be used in a proton exchange membrane water electrolysis hydrogen production device under a neutral environment at 1 Acm -2 The current density can be operated for 100 h at a low and stable cell potential of 1.62 V without decay.

Citation Information

Patent Citations

  • Preparation method of carbon-coated platinum oxygen reduction electrocatalyst

    CN115663210A

  • Rare earth element doped RuO2 material as well as preparation method and application thereof

    CN118127561A

  • Display device

    KR1020210066779A

  • Carrier-free oxygen reduction catalyst for use in low-temperature fuel cells and method for producing same

    US20230163316A1

  • Single-atom catalysts and method of manufacture thereof

    US20230366111A1